Analysis of high-voltage silicon vertical multi-junction solar cells: under concentrated illumination - Khalis, Mohamed; Masrour, Rachid (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
We analyze the J-V characteristics of silicon vertical multi-junction solar cells. The J-V characteristic data includes J0, RS, Rsh, n, and Jph, representing saturation current density, series resistance, shunt resistance, ideality factor, and photocurrent density, respectively, and are utilized to extract the parameters of these multi-junction solar cells. These parameters were recently acquired in a previous investigation. In our research, we developed a MATLAB code to investigate the efficiency variation with concentration using the nonlinear least-squares method, following a similar approach as the previous study. Our findings reveal that the algorithm effectively utilizes electrical parameters obtained through the nonlinear least-squares method, ensuring stable convergence and faithful replication of experimental J-V characteristics. Our findings indicate that an increase in light concentration from 1 to 100 suns leads to an efficiency improvement from 19.4 to 26.2%. However, beyond 100 suns, the efficiency declines from 26.2 to 17.3%. The most influential parameter in determining solar cell efficiency is the open-circuit voltage, Voc. Our experiments have shown an increase in this voltage with light concentration. For instance, its value changes from around 19.147 V at 1 sun to approximately 25.491 V at 500 suns.